Photomechanical effect in Zn(ii) and Cd(ii) 1D coordination polymers: photosalient to non-salient behaviour. Issue 86 (12th October 2022) - Khan, Samim; Naaz, Sanobar; Ekka, Akansha; Dutta, Basudeb; Roy, Sourav; Medishetty, Raghavender; Mir, Mohammad Hedayetullah
Abstract : Two Zn(ii )/Cd(ii ) 1D coordination polymers undergo [2+2] photodimerization, wherein Zn-CP shows mechanical motion and generates a free cyclobutane ligand, while Cd-CP does not. Abstract : A Zn(ii ) based one-dimensional (1D) coordination polymer (CP), [Zn( cis -1, 4-chdc)(4-nvp)] (1 ) { cis -1, 4-H2 chdc = cis -1, 4-cyclohexanedicarboxylic acid and 4-nvp = 4-(1-naphthylvinyl)pyridine}, undergoes a solid-state photochemical [2+2] cycloaddition reaction, accompanied by mechanical motion, wherein crystals show swelling, jumping, splitting and bursting upon UV irradiation, whereas the analogous Cd(ii ) CP [Cd( cis -1, 4-chdc)(4-nvp)] (2 ) does not show any such response under UV light, although it undergoes [2+2] photodimerization. The present study can certainly provide the fundamental understanding for designing smart photoactuating materials.